PENGGUNAAN MEDIA GAMBAR TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 38 PADANG - Dewi, Silvia Mardila; Utami, Wanda Andika; Afnita, Afnita (Universitas Negeri Surabaya, 2018)
This research is a qualitative research. Qualitative research is research that contains information or data obtained in the form of descriptions or sequences of words. This study aims to describe the use of picture media for description text writing skills of Class VII students of SMP Negeri 38 Padang. The method used in this research is descriptive method by describing the object of research based on the reality. The form of research used is classroom action research. Data collection in this study is by interview. The use of picture media on writing text description skills of class VII students of Padang Public Middle School 38 is very effective to be used to improve students' writing skills. In addition, it can also increase the average value of students, attract students' attention and interest in learning, and can help teachers in the learning process. This is because the use of varied media will cause the teaching and learning process to run conducively and the presence of interesting media can increase students' enthusiasm for learning.